Impact of Non-Performing Financing and Capital Adequacy on Profit Growth in Islamic Commercial Banks - Kori Saumanisa; Ridwansyah; Gustika Nurmalia (Mutanaqishah: Journal of Islamic Banking, 2025)
Purpose – This study aims to determine the effect of Non-Performing Financing and capital adequacy on profit growth partially and simultaneously. The population in this study was 14 Islamic commercial banks, with a sample of 12 Islamic commercial banks. Methodology – This type of research employs a quantitative approach with an explanatory research design, utilizing a data analysis methodology that includes panel data regression analysis, assisted by EViews analysis. Findings – The results of this study indicate that partially non-performing financing has a positive and significant impact on profit growth, while capital adequacy does not significantly affect profit growth. Simultaneously, non-performing financing and capital adequacy affect profit growth. Implication – The implication is that Islamic commercial banks need to focus more on managing non-performing financing due to its significant impact on profit growth, despite its positive influence.  In addition, although capital adequacy does not have a partial effect, bank management must still consider both factors simultaneously to ensure stability and sustainable profit growth. Originality – The originality of this study lies in its specific focus on Islamic commercial banks in Indonesia in the period 2020-2024, a period that includes the impact of the pandemic and economic recovery, as well as the use of panel data analysis to simultaneously explore the effect of non-performing financing and capital adequacy on profit growth.